Rapid assessment of cataract at pension pay points in South Africa. Issue 7 (18th June 2007) - Cook, Colin; Kluever, Herman; Mabena, Letty; Limburg, Hans
Abstract : Aim: To test a method for the rapid assessment of cataract blindness in South Africa. Design: Randomised cluster-based cross-sectional survey (20 clusters of 50 each). Setting: Pension pay points in Moretele district, North West Province, South Africa. Subjects: Female pensioners aged ⩾60 years, and male pensioners aged ⩾65 years. Outcome measures: (1) Prevalence of cataract requiring surgery; (2) prevalence of blindness due to cataract; (3) cataract surgical coverage; (4) cataract surgery outcome; and (5) barriers to cataract surgery. Results: 1000 pensioners were screened (681 women and 319 men). 17.2% of pensioners had operable cataract (visual acuity <6/60); 95% CI −3.4% to 3.4%); 15.6% of pensioners were blind due to cataract (95% CI −3.1% to 3.4%); and 5.6% of pensioners had had previous cataract surgery, 55.4% with intraocular lens implant and 44.6% without intraocular lens implant. The cataract surgical coverage was 24.6%. 80% of people who had had surgery were satisfied with the result, but 26.8% had a poor outcome according to the World Health Organization criteria. The main barrier to uptake of surgery was a lack of awareness of the availability of the surgery. Conclusions: Rapid assessment of cataract at pension pay points is a useful and effective tool for our district Vision 2020 programmes in South Africa. Steps need to be taken to raise awareness of the availability of cataract surgery among indigent pensioners, and to improve the quality of visual outcome after surgery by ensuring routine monitoring of postoperative visual acuity.